P07.02 Evaluation of the hologic transcription mediated amplification assay for detection of mycoplasma genitalium from urine samples. (13th September 2015) - Tabrizi, SN; Costa, AM; Su, J; Lowe, P; Bradshaw, CS; Fairley, CK; Garland, SM
Abstract : Introduction: M. genitalium is an emerging sexually transmitted pathogen, with a strong association with urethritis, cervicitis and pelvic inflammatory disease. Detection of this bacterium by routine culture is not practical and routine diagnosis and screening for M. genitalium by molecular techniques has been hampered by lack of readily available commercial assays. A preliminary version of a commercial amplification assay is currently available on the Panther platform and was evaluated against an in-house qPCR assay currently in use for routine diagnostics. Methods: Overall 1000 consecutive urine samples from men and women were utilised for this evaluation. Over the course of 3 months, urine samples were obtained from consecutive symptomatic men and women being screened for M. genitalium at Melbourne Sexual Health Centre, as well as women being screened prior to termination of pregnancy at the Royal Women's Hospital, Melbourne. The primary Hologic assay targeting 80bp region of 16s rRNA was compared to the in-house diagnostic assay which targets a 517bp region of 16S gene, as well as a second 16s rRNA target available on the Hologic platform. Results: The comparison of the two targets available on the Hologic platform showed very high correlation (k = 0.97 95% CI 0.93–1.00). Comparison of primary Hologic assay to in-house 16S qPCR assay, also showed very good correlation (K = 0.84 95% CI 0.75–0.93). Overall, both primary and secondary Hologic assays on Panther were more sensitive than the 16S qPCR for detection of M. genitalium in urine specimens. Conclusion: The M. genitalium assay on the Hologic platform integrated well with the laboratory procedures allowing rapid testing and possibility of rapid and accurate reporting using integration with laboratory information system. Overall the Hologic assay for detection of M. genitalium offers a simple, accurate and sensitive platform for diagnostic laboratories for detection of this important upcoming pathogen. Disclosure of interest statement: Hologic supplied the diagnostic kits and the Panther platform to conduct this study.